Preparation of the Elderly Population for Changing of Agricultural Labor Force in Chiang Mai Province - ฟองมูล, สายสกุล (วารสารการพัฒนาชุมชนและคุณภาพชีวิต, 2019)
This research on “Preparation of the Elderly Population for Changing of Agricultural Labor Force in Chiang Mai Province,” had the following objectives: To study the situation of the elderly population in agriculture in Chiang Mai province, to study the preparedness of the elderly laborers in agriculture in Chiang Mai province, and to seek guidelines in developing and strengthening the preparedness of the elderly laborers in agriculture in Chiang Mai province. The quantitative data was analyzed using descriptive statistics and qualitative data was analyzed using content analysis. In this research it showed the farmers developed themselves by having training at the Agricultural Training Center and also applied the principles of the King’s Sufficiency Economy Philosophy in their daily lives. Moreover, the elderly farmers have prepared by encouraging and supporting their children/descendants to study agriculture in the university with the hope that they would bring the knowledge in agriculture to develop their families. The study found that the farmers wanted the government and private sectors, educational institutions to support the elderly farmers in terms of health benefits, markets for agricultural products, management extension, encourage and instill the values of agriculture in educational institutions to create new generation farmers in the future.